PENGUATAN IDENTITAS BUDAYA DAN KETAHANAN MASYARAKAT MELALUI TRADISI MAGEBEG – GEBEGAN : KAJIAN KEARIFAN LOKAL DESA TUKADMUNGGA DALAM MENJAGA HARMONI SOSIAL DAN WARISAN PERADABAN BALI - Yanti, Putu Risma; Yudana, I Made; Pratiwi, Ni Luh Putu Ayu; Apriyani, Maulidah; Diska Subina , Diska; Wirayanti , Ni Kadek Ana; susanti , kadek (Program Studi PPKn Universitas Pendidikan Ganesha, 2025)
The Magebeg Gebegan tradition in Tukadmungga Village was a form of local wisdom that significantly strengthened cultural identity and community resilience amid modern development. This study revealed how this cultural custom helped maintain social harmony and sustainably preserved Balinese civilization values. To obtain the data, the research used a descriptive qualitative case study approach. In-depth interviews with traditional leaders and local residents, active observation during the Magebeg Gebegan ceremony, and reviews of local cultural documents were conducted. Qualitative data analysis was performed to determine the symbolic meaning and social function of the tradition. The study showed that Magebeg Gebegan was not merely a religious ritual, but also a way to enhance social solidarity, encourage community cooperation, and pass on ancestral values to the next generation. The tradition helped preserve local culture and strengthen social cohesion. Magebeg Gebegan was very important for maintaining Balinese culture at the village level. Amid globalization challenges, preserving this tradition provided a real contribution to social development based on local wisdom and cultural resilience.